2015
DOI: 10.1097/pcc.0000000000000520
|View full text |Cite
|
Sign up to set email alerts
|

End-of-Life Practices Among Tertiary Care PICUs in the United States

Abstract: Objective To describe variability in end-of-life practices among tertiary care pediatric intensive care units (PICUs) in the U.S. Design Secondary analysis of data prospectively collected from a random sample of patients (n=10,078) admitted to PICUs affiliated with the Collaborative Pediatric Critical Care Research Network (CPCCRN) between December 4, 2011 and April 7, 2013. Setting Seven clinical centers affiliated with the CPCCRN Patients Patients included in the primary study were <18 years of age, ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
57
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 92 publications
(68 citation statements)
references
References 29 publications
(49 reference statements)
8
57
1
2
Order By: Relevance
“…Detailed institutional data along with other analyses have been published. 13,21,2325 For additional details concerning patient and site level data, outcomes, and physiological data see the supplemental materials (Supplemental Description and Details of the TOPICC Study).…”
Section: Methodsmentioning
confidence: 99%
“…Detailed institutional data along with other analyses have been published. 13,21,2325 For additional details concerning patient and site level data, outcomes, and physiological data see the supplemental materials (Supplemental Description and Details of the TOPICC Study).…”
Section: Methodsmentioning
confidence: 99%
“…Clinical site was independently associated with likelihood of LWLS discussions. Prior CPCCRN research has shown that morality rate and mode of death did not vary significantly across sites when assessed during the same time period as the current study (35). The association between clinical site and LWLS discussions observed in this study may reflect variation in institutional practice, documentation of discussions, or other factors.…”
Section: Discussionmentioning
confidence: 52%
“…Most die in a hospital intensive care unit (ICU) via withdrawal or limitation of life-support (2, 3). Twenty percent of all pediatric deaths involve children with complex chronic conditions, and these children commonly require prolonged hospitalizations with ICU level care and mechanical ventilation (4, 5).…”
Section: Introductionmentioning
confidence: 99%